QUANTIFYING THE DIFFICULTY OF SPECIFIC MOVEMENTS IN THE STRADDLE VAULT FOR ELEMENTARY SCHOOL CHILDREN - Takashi Sano; Shohei Kokudo (Science of Gymnastics Journal)
The degree of difficulty of specific movements can be considered as movement information that teachers use to guide exercise instruction. The purpose of the present study was to quantify the difficulty of the movements comprising the straddle vault for 3rd and 4th grade elementary school children. A total of 538 children (263 boys, 275 girls from the 3rd and 4th grades participated in this study. Their straddle vault movements were recorded from both the left and front sides of the individuals and scored using an observational evaluation criterion. After confirming the unidimensionality of the items, item difficulty (b) was estimated using item response theory (IRT). Additionally, differential item functioning (DIF) was investigated to determine whether the difficulty varied depending on grade level. The following findings emerged from estimating the difficulty levels using IRT: Movements involving taking off from a stable run-up (b = -4.952 to -1.833) and shifting weight forward (b = -0.610 to -0.048) were classified as low-difficulty. Movements requiring a bouncy take-off (b = 0.131 to 0.360) and stable landing (b = 0.012 to 0.816) were of medium difficulty. Regarding landing, DIF was detected, indicating that this movement was more difficult for 3rd graders than for 4th graders. Movements involving turning rotation (b = 1.026 to 1.309) and landing aggressively (b = 1.152 to 1.806) were categorized as high-difficulty. Dynamic take-off movements were identified as extremely difficult (b = 2.432 to 3.824). In conclusion, it is necessary to develop a teaching program that accounts for the difficulty of these movements and to verify its effectiveness.